(untitled) (International Journal of Physiotherapy, 2015)
Background: Stretching used as a technique for injury prevention in the clinical settings, the study aimed to determine the early findings of hamstring tightness with both groups in the population, now a days the sedentary activities like prolonged sitting might cause hamstring tightness and change in path kinematics of gait intern lead to postural defects and back pain, understanding of the stretching helps clinician to make decisions for rehabilitation. Methods: Across-sectional study, counterbalanced with repeated-measures , one group with static stretch – (double hamstring stretch and hurdlers stretch) for 3 times,30seconds subsequently in another group PNF contract relax(agonist contraction) technique for 10 seconds position and 10 seconds stretch repeated for 3 times. Results: The results from data and statistical analysis by using t-test, SPSS obtained by using goniometer are tabulated in terms of mean, standard deviation and p-value in both groups. In experimental group flexion with PNF showed improvement 9.27±1.91(right side), 9.53±2.42(left side) and static stretching showed 7.8±2.91(right side), 7.47±1.96(left side) this proves that PNF has consistent improvement than static stretching Conclusions: Static and proprioceptive neuromuscular facilitation stretching both have produced greater improvement but compared with PNF contract relax(agonist) stretching showed significant change in hamstring flexibility compared with control group . The effect sizes, however corresponding to these stretching-induced changes were small, which suggests the need for practitioners to consider a risk-tobenefit ratio when incorporating static or proprioceptive neuromuscular facilitation stretching.